Level Of Community Knowledge About The Use Of Vitamin C And Proper Storage Of Medicine In Rt 06 Cawang Village - Frida Octavia Purnomo; Khuzaimah Farradilla Mutaqin; Kartika Rahma; Intan Permata Sari (Universitas Binawan, 2022)
Knowledge about drugs is very important among the community, especially how to consume vitamin C and how to store drugs properly and correctly at home so that the drugs that will be consumed do not get damaged quickly or reduce their efficacy. The method used is direct observation using questionnaires and leaflets. The people of RT 06/RW 06 Cawang know about the proper and correct way of storing medicines. The results of this study show that there are 54.5% of people who already know how to store it properly and 80% of people who already understand the importance of drinking vitamin C during the pandemic, so that the body is protected from various viruses that will enter the body.